2012
DOI: 10.2528/pierm12080308
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Plasma Column Cross-Section Non-Circularity on the Excitation of the Azimuthal Surface Waves in Electron Cyclotron Frequency Range by Annular Electron Beam

Abstract: The initial stage of interaction between an annular beam of electrons, which rotate along Larmor orbits in the gap between a localized plasma column and a metal waveguide with a circular crosssection of its walls, and the electromagnetic waves of the surface type, is studied theoretically. These waves are extraordinary polarized; they propagate along the azimuthal angle across an axial external steady magnetic field in the electron cyclotron frequency range. The numerical analysis shows that changing the shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Usually, the toroidicity of the external magnetic field B 0 is accompanied by a shift of the plasma column axis from the waveguide axis and a change of the plasma column cross-section. But these two effects on the excitation of the azimuthal surface modes have been studied in [22], and therefore they were out of the scope of this paper. It is shown that the toroidal non-uniformity of B 0 affects most essentially the dispersion properties of the LF ASWs when their eigen frequency is close to the absolute value of the electron cyclotron frequency.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, the toroidicity of the external magnetic field B 0 is accompanied by a shift of the plasma column axis from the waveguide axis and a change of the plasma column cross-section. But these two effects on the excitation of the azimuthal surface modes have been studied in [22], and therefore they were out of the scope of this paper. It is shown that the toroidal non-uniformity of B 0 affects most essentially the dispersion properties of the LF ASWs when their eigen frequency is close to the absolute value of the electron cyclotron frequency.…”
Section: Discussionmentioning
confidence: 99%